Radiocarbon dating and its applications in Chinese archeology: An overview - Chen, Xianglong (Frontiers in Earth Science, 2023)
Radiocarbon dating is a well-established chronometric technique that has been widely employed in Chinese archeology since the first radiocarbon laboratory started operating in the Institute of Archaeology at the Chinese Academy of Sciences in 1965. In the three decades of studies that followed, achievements were made in radiocarbon dating, especially in measurement techniques, sample preparation, and the establishment of regional chronological frameworks. There is no doubt that Chinese archeology entered a golden age with the assistance of radiocarbon dating techniques at the beginning of the 2000s. It is, however, also true that compared to Western countries, China has reported far fewer radiocarbon dates than expected. This paper presents an overview of the history of the radiocarbon dating technique and its significant applications in Chinese archeology, focusing on the transition from β-decay counting to accelerator mass spectrometry. Some of the breakthroughs in studies of the Upper Paleolithic, early Homo sapiens, neolithization, and the Xia and Shang dynasties are highlighted. We conclude the paper with a brief discussion of future work and research directions that need to be explored.